Role of Affective Factors in the Development of Productive Skills - Mihaljević Djigunović, Jelena (Array, 2007)
The chapter focuses on the relationship between affective learner characteristics and speaking and writing competence of EFL learners at the end of primary (year eight) and secondary education (year twelve). In the study the performance on communicative speaking and writing tasks of 80 year eight and 190 year twelve EFL learners was assessed. The following aspects of speaking performance were assessed: task achievement, choice and appropriacy of vocabulary, accuracy and fluency. Writing performance was assessed in terms of task achievement, range of vocabulary, accuracy and text structure.